PENGARUH AUDIT INTERNAL TERHADAP PENCEGAHAN KECURANGAN DALAM LAPORAN KEUANGAN - Fachruroji, Aji Ahmad (Jurnal Akuntansi UMMI, 2020)
This study aims to determine the effect of internal audits of the Prevention of Fraud in the financial statements. Variables used in this research is the Internal Audit and Fraud Prevention in the financial statements. The sample used internal auditor and accounting are 8 PT Selamat Lestari, PT PLN area of Sukabumi 7, PDAM Tirta Bumi Authority 9, PT Parrasindo Perkasa 7 No 31 the total number of samples . The analysis used is simple regression analysis. The analysis is used to determine signifikat. With 0,000 signifikat value <0.005, which means Ho rejected and Ha accepted, the Internal Audit signifikat effect on the Prevention of Fraud in the financial statements.